Conflict of laws in international arbitration - Ferrari, Franco, 1965-; Kröll, Stefan (Stefan Michael) (Sellier, 2011)
HauptbeschreibungIrrespective of the increasing harmonization of law at the transnational level, every arbitration raises a number of confl ict of laws problems relating to procedural questions as well as to issues concerning the merits of the case. Unlike a state court judge, the arbitrator has no "lex fori" in the proper sense providing the relevant confl ict rules to determine the applicable law. This raises the question of what confl ict of laws rules to apply and, consequently, of the extent of the freedom the arbitrator enjoys in dealing with this and related issues. The best example of.